Successful Blue Economy Examples With an Emphasis on International Perspectives - Wenhai, Lu; Cusack, Caroline; Baker, Maria; Tao, Wang; Mingbao, Chen; Paige, Kelli; Xiaofan, Zhang; Levin, Lisa; Escobar, Elva; Amon, Diva; Yue, Yin; Reitz, Anja; et al. (Frontiers in Marine Science, 2019)
Careful definition and illustrative case studies are fundamental work in developing a Blue Economy. As blue research expands with the world increasingly understanding its importance, policy makers and research institutions worldwide concerned with ocean and coastal regions are demanding further and improved analysis of the Blue Economy. Particularly, in terms of the management connotation, data access, monitoring, and product development, countries are making decisions according to their own needs. As a consequence of this lack of consensus, further dialogue including this cases analysis of the blue economy is even more necessary. This paper consists of four chapters: (I) Understanding the concept of Blue Economy, (II) Defining Blue economy theoretical cases, (III) Introducing Blue economy application cases and (Ⅳ) Providing an outlook for the future. Chapter (II) and Chapter (III) summarizes all the case studies into nine aspects, each aiming to represent different aspects of the blue economy. This paper is a result of knowledge and experience collected from across the global ocean observing community, and is only made possible with encouragement, support and help of all members. Despite the blue economy being a relatively new concept, we have demonstrated our promising exploration in a number of areas. We put forward proposals for the development of the blue economy, including shouldering global responsibilities to protect marine ecological environment, strengthening international communication and sharing development achievements, and promoting the establishment of global blue partnerships. However, there is clearly much room for further development in terms of the scope and depth of our collective understanding and analysis.